Exploring Causality Between Bone Mineral Density and Cervical Spondylosis: Bidirectional and Multivariable Mendelian Randomization Study - Mao W; Wu L (Journal of Pain Research)
Wangnan Mao, Lianguo Wu The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, People’s Republic of ChinaCorrespondence: Lianguo Wu, Email mdwu8535@126.comBackground: Recent evidence has suggested a potential link between bone mineral density (BMD) and cervical spondylosis (CS), while the specific relationship has yet to be comprehensively elucidated. Our study aimed to implement a comprehensive analytical framework incorporating bidirectional two-sample Mendelian randomization (MR) and multivariable MR (MVMR) to investigate the causal relationship between BMD and CS.Methods: Genome-wide association summary statistics for BMDs across four skeletal sites and five age groups, and CS, were obtained from public databases. Single Nucleotide Polymorphisms (SNPs) that had a significant genetic association with exposures were used as instrumental variables (IVs). We employed inverse variance weighting (IVW) analysis as the primary analytical method to estimate potential causal effects, whereas Weighted median, MR-Egger regression, weighted mode, and simple mode were served as supplements. Furthermore, several sensitivity analyses (MR-Egger intercept, MR-PRESSO, Cochran’s Q test, and Leave-one-out test) were utilized to assess the robustness, heterogeneity, and horizontal pleiotropy of the findings.Results: After applying the Bonferroni correction, BMDs in three skeletal sites exhibited significant positive causal associations with CS risk, including total body (TB), femoral neck (FN), and heel bone (HB). Notably, based on MR analyses of TB-BMD data stratified by five age brackets, the positive causal relationship was especially pronounced in the 45– 60-year-old group. Further MVMR analysis revealed that, even after controlling for confounding factors, higher TB-BMD (OR = 1.14, 95% CI: 1.01– 1.29; P = 3.12E− 02) and HB-BMD (OR = 1.11, 95% CI: 1.01– 1.22; P = 2.45E− 02) still maintained an independent and significant causal association with CS. However, we did not find evidence to suggest that CS has an impact on BMD in reverse MR analysis.Conclusion: This study provides genetic support for a causal relationship between BMD and CS susceptibility. Specifically, individuals with high BMD are at greater risk of developing CS, offering valuable insights for future clinical research.Keywords: cervical spondylosis, bone mineral density, Mendelian randomization